Trust: Tacit Strategy in Organizational Management - Suárez-Morales, Lizbeth (2021)
The objective of this article is to reflect from the theories of Management and Social Psychology on the concept of trust in organizational management, those tacit elements that frame performance. Coleman’s Rational Action Theory, Simon’s Organizational Management Theory and Mintzberg’s Organizational Structure Theory. The methodology was based on the qualitative approach, the type of research was exploratory, using the technique of documentary analysis of bibliographic review in the database of Scopus and classic authors related to the topic. 232 small businesses were tested. By way of conclusion, organizational trust consolidates the management and strategy of the institutional fabric, as a tacit substantial part from the schools of thought of functional administration. Equilibrium theory, the theory of cognitive limits, which proposes confidence as an organization’s performance strategy.